2014
DOI: 10.4236/ojer.2014.32011
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Prediction for Earthquake in Bangladesh: Just How Big Does the Earthquake Have to Be Next Years?

Abstract: Earthquakes are more deadly than any other form of natural hazard. Because of this, scientists have been searching for accurate ways to predict earthquakes so that lives can be saved. Statistical analysis is useful methods of predicting earthquakes. They provide additional insights to the seismic hazard. In this work, the statistical analysis has been described through the study of "Region of Bangladesh". A sample result from the statistical analysis which gives intermediate term prediction of earthquakes is g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…However, the success ratio of the prediction was not clear in their research. Shongkour Roy et al performed statistical analysis using the Weibull distribution and Maximum Likelihood Estimation technique for calculation [13] and predicted that the probability of damaging structures by the earthquake by 2007 was 62%. Another research work by V.G.…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the success ratio of the prediction was not clear in their research. Shongkour Roy et al performed statistical analysis using the Weibull distribution and Maximum Likelihood Estimation technique for calculation [13] and predicted that the probability of damaging structures by the earthquake by 2007 was 62%. Another research work by V.G.…”
Section: Related Researchmentioning
confidence: 99%
“…All these zones created earthquakes, depending on their positions. A chronological analysis of important earthquakes in Bangladesh has been established by some of the researchers [13][14][15] and included in Bangladesh, as illustrated by Fig. 2 which displays the earthquake intensity in different faults.…”
Section: Introduction: 1background Of Earthquakesmentioning
confidence: 99%
“…Yépez and Yépez (2017) found that substandard construction materials and poor construction practice were some of the main reasons behind the collapse of thousands of buildings after Parameter estimates of the model: factors affecting earthquake load vulnerability c t-stat of the model: factors affecting vertical load vulnerability d t-stat of the model: factors affecting earthquake load vulnerability the Ecuador earthquake in 2016. Bangladesh has not experienced a major earthquake since Great Indian Earthquake 1897 (Roy 2014;Chakravorti et al 2015). But the country should be careful to maintain its construction quality in order to reduce vertical as well as earthquake load vulnerability to avoid a potential future disastrous situation.…”
Section: Study Findingsmentioning
confidence: 99%
“…However, the structural load bearing elements of these building stocks must perform adequately not only under vertical loads but also under lateral seismic loads due to the anticipated risks of seismic events in the vicinity of moderately active tectonic faults. [8][9][10][11] Unfortunately, in contrast, Bangladesh has had catastrophic building collapses in recent history under only vertical loads (Miller 12 for 2005 Spectrum Sweater Factory collapse, Yardley 13 for 2013 Rana Plaza collapse) due to poor construction quality with BAC. Even though the Bangladesh construction industry can transition toward better construction practices with SAC using imported stone aggregates, the significant stocks of old RC construction from BAC demand a thorough performance assessment for disaster risk mitigation.…”
Section: Introductionmentioning
confidence: 99%
“…Nakajima et al 7 found that the concrete compressive strength (fc) of 44% of the cores taken from 20 buildings in Dhaka was below 10 MPa. However, the structural load bearing elements of these building stocks must perform adequately not only under vertical loads but also under lateral seismic loads due to the anticipated risks of seismic events in the vicinity of moderately active tectonic faults 8–11 . Unfortunately, in contrast, Bangladesh has had catastrophic building collapses in recent history under only vertical loads (Miller 12 for 2005 Spectrum Sweater Factory collapse, Yardley 13 for 2013 Rana Plaza collapse) due to poor construction quality with BAC.…”
Section: Introductionmentioning
confidence: 99%